Practice Variation in Anticoagulation Prescription and Outcomes After Device-Detected Atrial Fibrillation: Insights From the Veterans Health Administration. Issue 22 (28th May 2019) - Perino, Alexander C.; Fan, Jun; Askari, Mariam; Heidenreich, Paul A.; Keung, Edmund; Raitt, Merritt H.; Piccini, Jonathan P.; Ziegler, Paul D.; Turakhia, Mintu P.
Abstract : Background: Device-detected atrial fibrillation (AF) is associated with increased risk of stroke; however, there are no clearly defined thresholds of AF burden at which to initiate oral anticoagulation (OAC). We sought to describe OAC prescription practice variation in response to new device-detected AF and the association with outcomes. Methods: We performed a retrospective cohort study using data from the Veterans Health Administration linked to remote monitoring data that included day-level AF burden. We included patients with cardiac implantable electronic devices and remote monitoring from 2011 to 2014, CHA2 DS2 -VASc score ≥2, and no prior stroke or OAC receipt in the preceding 2 years. We determined the proportion of patients prescribed OAC within 90 days after new device-detected AF across a range of AF thresholds (≥6 minutes to >24 hours) and examined site variation in OAC prescription. We used multivariable Cox proportional hazards regressions to determine the association of OAC prescription with stroke by device-detected AF burden. Results: Among 10 212 patients with cardiac implantable electronic devices, 4570 (45%), 3969 (39%), 3263 (32%), and 2469 (24%) had device-detected AF >6 minutes, >1 hour, >6 hours, and >24 hours, respectively. For device-detected AF >1 hour, 1712 patients met inclusion criteria (72±10 years; 1.5% female; CHA2 DS2 -VASc score 4.0±1.4; HAS-BLED score 2.6±1.1). The proportion receiving OAC varied based on device-detected AF burden (≥6 minutes: 272/2101 [13%]; >1 hour: 273/1712 [16%]; >6 hours: 263/1279 [21%]; >24 hours: 224/818 [27%]). Across 52 sites (N=1329 patients), there was substantial site-level variation in OAC prescription after device-detected AF >1 hour (median, 16%; range, 3%–67%; median odds ratio, 1.56 [95% credible interval, 1.49–1.71]). In adjusted models, OAC prescription after device-detected AF >24 hours was associated with reduced stroke risk (hazard ratio, 0.28; 95% CI, 0.10–0.81; P =0.02), although the propensity-adjusted model was significant when AF lasted at least 6 minutes. Conclusions: Among veterans with cardiac implantable electronic devices, device-detected AF is common. There is large practice variation in 90-day OAC initiation after new device-detected AF, with low rates of treatment overall, even for episodes that last >24 hours. The strongest association of OAC with reduction in stroke was observed after device-detected AF >24 hours. Randomized trials are needed to confirm these observational findings. Abstract : Supplemental Digital Content is available in the text.